2017
DOI: 10.1371/journal.pone.0188922
|View full text |Cite
|
Sign up to set email alerts
|

Demographic monitoring of wild muriqui populations: Criteria for defining priority areas and monitoring intensity

Abstract: Demographic data are essential to assessments of the status of endangered species. However, establishing an integrated monitoring program to obtain useful data on contemporary and future population trends requires both the identification of priority areas and populations and realistic evaluations of the kinds of data that can be obtained under different monitoring regimes. We analyzed all known populations of a critically endangered primate, the muriqui (genus: Brachyteles) using population size, genetic uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
0
29
0
4
Order By: Relevance
“…It can also be argued that there are advantages to keeping some field sites free of scientific monitoring. Strier et al argue that researchers should consider local context and the ramifications of habituation and/or bringing attention to a given primate populations. They suggest that researchers assess both the scientific and conservation value of monitoring primate individuals.…”
Section: Moving Forwardmentioning
confidence: 99%
“…It can also be argued that there are advantages to keeping some field sites free of scientific monitoring. Strier et al argue that researchers should consider local context and the ramifications of habituation and/or bringing attention to a given primate populations. They suggest that researchers assess both the scientific and conservation value of monitoring primate individuals.…”
Section: Moving Forwardmentioning
confidence: 99%
“…While the northern‐most B. arachnoides population overlaps B. hypoxanthus latitudinally at Parque Nacional da Serra dos Órgãos (PARNASO) and Parque Estadual do Desengano in Rio de Janeiro (Cunha, Grelle, & Boubli, ), the species are nonetheless separated by approximately 160 km to both the east (PARNASO) and south (São Francisco Xavier, SP). Given the geographic proximity between southern and northern muriqui populations both in Rio de Janeiro and São Paulo—and given the large extent of forest remnants in this region—it is still plausible that a small contact zone exists between the two species in this region (Strier et al, ), a possibility that is also suggested by species distribution models (Ingberman et al, ). Future research in the region near the PNI is warranted to better characterize this population, primarily focusing on a possible hybrid zone.…”
Section: Discussionmentioning
confidence: 96%
“…(a) Inset of South America highlighting Brazil (green), the Atlantic Forest domain (light green), and an approximated region where muriquis are found (rectangle). (b) Historic distribution of B. hypoxanthus (pink polygons) and B. arachnoides (brown polygon) according to (Ingberman et al, ; Strier et al, ). Yellow dots mark sampling sites for northern and southern muriquis, respectively, and crosses mark unsampled muriqui sites based on recent surveys (Jerusalinsky et al, and references therein).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, almost 80% of the total localities of Atlantic Forest where muriquis ( Brachyteles spp.) presently inhabit are protected areas (private or governmental—state and federal units, Strier et al, 2017 ). In Central Africa, a long-term study (2007–2014) in which camera traps were used to census terrestrial mammals found strong evidence of stability in several threatened African primates such as the l’Hoest’s monkey, mandrills ( Mandrillus sphinx ) and chimpanzees ( Beaudrot et al, 2016 ).…”
Section: Landscape Approaches To Primate Conservationmentioning
confidence: 99%